ANALISIS KEBUTUHAN LINGKUNGAN SEKOLAH SEBAGAI LABORATORIUM PADA PEMBELAJARAN IPA SEKOLAH DASAR - Sarwindah, Sarwindah; Khosiyono, Banun Havifah Cahyo; Nisa, Ana Fitrotun; Cahyani, Berliana Henu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Class 3 thematic learning at SDN 1 Karangwuni still uses the 2013 curriculum, where the teacher still uses a classical approach, namely the teacher dominates the learning process, there is less student activity. The students only sit and pay attention, taking notes and answering questions from the teacher, while the teacher only delivers the material through lectures. and discuss questions with students. This is what makes students bored and does not understand the material so that student activities and learning are less than optimal. The aim of this research is to use the school environment as a science laboratory to increase the activities and learning outcomes of class III students at SDN 1 Karangwuni for the 2023/2024 academic year. This type of research is Classroom Action Research (PTK) which is carried out in 2 cycles consisting of planning, implementation, observation and reflection. There are 2 types of data used in this research, namely: quantitative and qualitative data. Quantitative data is in the form of observation sheets on the implementation of lesson plans, observations of teacher and student activities in the learning process and student activity questionnaire sheets, while quantitative data is obtained from the results of evaluating student learning outcomes tests given at the end of each cycle to obtain data regarding student learning outcomes. From research results shows that there is increased activity in thematic learning of science subjects by using the school environment as a science laboratory. In cycle I it was 70% in the high category and increased in cycle II to 80% in the very high category. Improvements were also seen in student learning outcomes, in cycle I the classical completeness achieved was 70% and in cycle II it increased to 90% in the complete category. So it can be concluded that using the school environment as a science laboratory can improve the activities and thematic learning outcomes of the 2013 curriculum for class III students at SDN 1 Karangwuni for the 2023/2024 academic year.